Fritillaria meleagris L. (Liliaceae) in the Kharkiv Region: ecological preferences, conservation problems - Bezrodnova, O.; Ivanova, K. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2023)
Fritillaria meleagris L. is a рalearctic species with a disjunct distribution. It is protected at the national level in Ukraine, listed as "vulnerable" in the Red Data Book. Most of the data on the species distribution, as well as on the status and stability of its populations, have been obtained for the Carpathian region. Much less information is available for F. meleagris in the Forest Steppe, especially for its left-bank part. The article presents the results of the study of the peculiarities of F. meleagris distribution in the Kharkiv Region and provides information on the structure of coenopopulations and their ecological and coenotic preferences. Problems and prospects for this species conservation are also considered. The studies cover the biotopes of the Merla River valley and its tributary, the Merchyk River (the Dnipro River basin) in an area of more than 35 square km. In the Kharkiv Region, the F. meleagris coenopopulations were found mainly in grass-type biotopes. These are usually secondary post-forest meadows of the Molinio-Arrhenatheretea Tx. 1937 class. Only one coenopopulation is located in a tree-type biotope (mixed floodplain forest with Quercus robur L., Ulmus laevis Pall., Alnus glutinosa (L.) Gaertn., Salix alba L., Padus avium Mill., Populus аlba L., P. deltoides Marshall, P. tremula L., Acer negundo L., А. tataricum L., A. campestris L., without a pronounced dominant). The specificity of the ecological regimes of the studied localities of F. meleagris has been clarified by the phytoindication method. As a rule, they are damp (less often, fresh) forest-meadow habitats with full, but uneven (temporarily excessive) wetting of the root layer of the soil. The soils are moderately aerated, weakly acidic (pH 5.5–6.5), enriched with salts, but with insignificant carbonate content, and often relatively poor in terms of mineral nitrogen. The climate is characterized by submicrothermal conditions with signs of subaridity and subcontinentality. We have not detected any significant variability of conditions (both edaphic and climatic) in the studied localities. They are more or less optimal for the existence of F. meleagris. In all the F. meleagris localities studied, the change in the hydrological regime due to the reclamation of floodplain remains a risk factor but does not pose an immediate threat. The existence of forest coenopopulations in glades is threatened by overgrowth of trees and shrubs (the invasion of Populus tremula and Acer negundo is particularly dangerous). The decrease in the number of meadow coenopopulations is a result of plowing and burning. Currently, in the Kharkiv Region, F. meleagris is protected in Slobozhanskyі National Nature Park (1 locality) and in Kapranskyі Botanical Reserve of local importance (11 localities). Monitoring of the existing localities outside the protected areas and their inclusion into the expansion zone of the Slobozhanskyі National Nature Park is an important condition for their preservation.